2021
DOI: 10.2174/0929867327666201103162239
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Fak and Fak Inhibitors

Abstract: Background: Focal adhesion kinase (Fak) is a cytoplasmic protein tyrosine kinase overexpressed and activated in different solid cancer; it showed important role in metastasis formation, cell migration, invasion and angiogenesis and consequently it has been proposed as a potential target in cancer therapy, particularly in a metastatic phase. In recent years different investigations highlight the importance of new Fak inhibitors as potential anti-cancer drugs, but other studies evidenced its role in different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…Spebrutinib shares a common diphenylaminopyrimidine (DPPY) pharmacophore with several tyrosine kinase inhibitors, such as Alk [ 31 ], focal adhesion kinase (FAK) [ 32 ], and EGFR inhibitors [ 33 , 34 ]. It is under study in combination with FAK inhibitors to treat solid tumors (particularly esophageal cancer) [ 35 ].…”
Section: Btkis In Clinical and Pre-clinical Evaluationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spebrutinib shares a common diphenylaminopyrimidine (DPPY) pharmacophore with several tyrosine kinase inhibitors, such as Alk [ 31 ], focal adhesion kinase (FAK) [ 32 ], and EGFR inhibitors [ 33 , 34 ]. It is under study in combination with FAK inhibitors to treat solid tumors (particularly esophageal cancer) [ 35 ].…”
Section: Btkis In Clinical and Pre-clinical Evaluationsmentioning
confidence: 99%
“…As previously reported, the diphenylaminopyrimidine core has been deeply investigated as a chemical scaffold that is useful in the synthesis of most kinase inhibitors [ 31 , 32 , 33 , 34 ]. Currently, Spebrutinib is the most promising compound of these analogues.…”
Section: Recent Advances In Btkismentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that FAK contains multiple functional phosphorylation sites (Tyr397, Tyr407, Tyr576, Tyr577, Tyr861, Tyr925), of which Tyr397 is one of the most important phosphorylation site [ 9 ] and interacts directly with the Src family. Tyr576 and 577 are in the activation loop of the kinase domain, which are the main sites can be phosphorylated by Src family [ 9 ]. Tyr925 is phosphorylated and binds to the junction protein Grb2 to make FAK aggregate with integrins, while Tyr397 and Tyr 861 both could recruit other SH2 proteins [ 10 ].…”
Section: Fak Structural Features and The Function In Cancermentioning
confidence: 99%
“…Over the past decades, multiple preclinical and clinical-stage FAK inhibitors have been assessed for their effects in treating cancer diseases [ 9 , 15 , 32 , 33 ]. Table 1 summarized five oral ATP-competitive FAK inhibitors that have been evaluated in clinical trials.…”
Section: The Development Of Fak Inhibitorsmentioning
confidence: 99%